Are Templates Killing the Subtitling Principles? Subtitlers’ Views on the Impact of Templates on the Media Localisation Industry - Skwarek, Aleksandra; Szarkowska, Agnieszka; Szkriba, Sonia (Journal of Audiovisual Translation, 2024)
The subtitling industry has witnessed remarkable growth in recent years, driven by the upsurge in streaming content. To streamline the subtitling process, international streaming companies turned to using subtitling templates in their multilingual workflows. However, the introduction of templates has brought about a new set of challenges, affecting the skills required of subtitlers and the quality of the resulting translations. In this study, we use semi-structured interviews with professional subtitlers to gauge their perspective on working with contemporary template-based workflows and assess the impact of templates on the translation process and the quality of the final product. We were particularly interested in how templates influence translation, aligning with our central research question, whether templates kill fundamental subtitling principles. The findings reveal that subtitlers do not inherently oppose templates but emphasise the necessity for high-quality templates and annotations, especially for pivot workflows. Key concerns include issues with quality, tight deadlines, and inadequate compensation, along with the way in which template-based workflows are implemented. The study shows the importance of a collective commitment from all industry stakeholders to ensure high-quality outcomes and to position templates as valuable tools in the subtitling industry. The insights gained from the study are relevant to enhancing the visibility of subtitlers within the industry, as well as for evaluating the current state of the industry and establishing the foundation for identifying best practices. Lay summary The subtitling industry has seen significant growth, largely due to the increase in streaming content. To make translating subtitles more efficient, international streaming companies have started using templates. However, this has brought new challenges, affecting the skills subtitlers need and the quality of translations they produce. In our study, we interviewed professional subtitlers to understand their perspective on using these modern template-based workflows and to see how templates affect the translation process and the quality of the final product. We were particularly interested in how templates impact both the translation process and the quality of the final product, which aligns with the central question of our paper: are templates killing fundamental subtitling principles? Our findings show that subtitlers don’t dislike templates, but they stress the importance of having high-quality templates. Some main concerns include problems with template quality, tight deadlines, and inadequate pay, as well as how template-based workflows are put into practice. This study emphasizes the need for everyone in the industry to work together to ensure high-quality results and to establish templates as valuable tools in the subtitling field. The insights from this study can help make subtitlers more visible in the industry, evaluate the current state of the field, and lay the foundation for best practices.